Perbedaan Pengetahuan Balance Scorecard, Motivasi, dan Kompensasi Kinerja dalam Penerapan Keberhasilan Balance Scorecard (Studi pada Sekolah Singapore National Academy) - Maria Kumalasari; Dwi Suhartini (Journal of Economics, Business, and Government Challenges, 2018)
This research aims to examine the different of balance scorecard’s level of understanding, work motivation and performance compensation toward the success of balanced scorecard’s implementation. The better the understanding of balanced scorecard, motivation and performance compensation are expected to increase the use of performance measures that lead to the success balanced scorecard implementation. The implementation of balanced scorecard success is shown in the use of common and unique performance measures in a balance way. The data collection method used 2x2x2 factorial experimental design, with 48 participants from Singapore National Academy School. Data analysis was performed by two-way ANOVA test. The results show that the level of understanding of the balanced scorecard and performance compensation cause differences in the success of balanced scorecard. Whereas extrinsic and intrinsic motivation do not cause differences in the success of balanced scorecard.